2012
DOI: 10.1002/ajp.22047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Kinship Patterns in a Population of Black Howler Monkeys,Alouatta pigra, atPalenqueNationalPark,Mexico

Abstract: We investigated the genetic structure and kinship patterns of black howler monkeys (Alouatta pigra) at Palenque National Park, Mexico. Fecal samples from 49 individuals residing in eight social groups were successfully genotyped for 19 polymorphic microsatellite markers known to be variable in other ateline primates. Overall, genetic diversity was low (H(o) = 0.588) with an average of 4.2 alleles per loci (range = 2-8). We found that intergroup genetic variation among adults was relatively high (mean between-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 58 publications
3
33
0
3
Order By: Relevance
“…There is also evidence from monotokous (single young at a time) group‐living animals with high paternity concentration, where paternal half‐siblings are numerous and have the opportunity to co‐disperse and form long‐term alliances, moving from group to group (Pope 1990; van Belle et al. 2012). …”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence from monotokous (single young at a time) group‐living animals with high paternity concentration, where paternal half‐siblings are numerous and have the opportunity to co‐disperse and form long‐term alliances, moving from group to group (Pope 1990; van Belle et al. 2012). …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, A. palliata females are reported to disperse from their natal group and join groups that do not contain kin, but exceptions exist where individuals sometimes stay in their natal group [Glander, 1980; Clarke & Glander, 2008]. Regarding males, different group-joining strategies have been reported in A. pigra ; whereas in some cases a single male can join a group without evicting any residents, in other instances a single male may take over a group by expelling the resident males [Horwich et al, 2000; Van Belle et al, 2012], or closely related males can form coalitions and take over a group together [Van Belle et al, 2012]. In contrast to the multiple strategies reported in A. pigra , the dispersal strategies of A. palliata males are reported to be similar to that of A. palliata females, with individuals dispersing before adulthood, remaining solitary for some time, and joining groups that do not contain kin [Glander, 1980; Glander, 1992; Clarke & Glander, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, A. arctoidea females in coalitions with kin enjoy higher reproductive success than those in coalitions with unrelated females (Pope 2000b ). Similar forms of female-female competition have also been observed in A. caraya (Calegaro-Marques and Bicca-Marques 1996 ) and A. pigra (Van Belle et al 2011 ;Brockett et al 1999 ), and females have been reported to co-reside with kin in some groups of A. pigra (Van Belle et al 2012 ), A. caraya (Oklander et al 2010 ), and A. palliata (Milton et al 2009 ). It is unknown to what extent female-female competition in howler monkeys has selected for weaponry and larger bodies, and how it infl uences sexual dimorphism.…”
Section: Intragroup Mating Patternsmentioning
confidence: 64%
“…Intragroup male-male competition in multimale groups might be considerably lower among resident male who are kin compared to those who are not, as males accrue inclusive fi tness benefi ts as a consequence of the mating behavior of relatives. Genetic studies have revealed that adult males who are closely related co-reside in some bisexual groups in A. pigra (Van Belle et al 2012 ), A. caraya (Oklander et al 2010 ), A. palliata (Milton et al 2009 ), and A. arctoidea (Pope 1990 ). In addition, male coalitions of related individuals in multimale A. arctoidea groups last longer and accrue greater fi tness than coalitions of unrelated resident males (Pope 1990 ).…”
Section: Conclusion and Prospectsmentioning
confidence: 97%